A Critical Review of the Book of Administrative Law - Ghazale Taheri Attar; MohammadAli HasaniNik (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The science of law is bound to examine the state of affairs of each country and to design the relations of government agencies with one another and with the people, in order to achieve the best conditions for the prosperity and improvement of any civilization. The Book of Administrative Law is the work of Bijan Abbasi, one of the last authors in this field that tries to explain the basics of administrative law knowledge to researchers and practitioners in the six chapters. In this article, through a fair study, review and critique of this work, we sought to identify its strengths and weaknesses and to help improve the state of administrative law knowledge and consequently improve the administrative structure of the country. This book seems to have been written for the general public, as it has not been deeply embedded in any of the dimensions, theoretical foundations, administrative structures of the Islamic Republic, and the administrative structures of the Islamic Republic in comparison with other leading countries in administrative law, and especially for law students. It is not useful and can only be a gateway to knowledge of administrative law.